Hemangioma – A pointer to Abernethy syndrome? - Shyam S Kothari (Annals of Pediatric Cardiology, 2020)
Diffuse pulmonary arteriovenous malformations or pulmonary arterial hypertension (PAH) may result from congenital portosystemic venous shunts. Hemangioma as a physical sign of congenital portosystemic shunts (like Abernethy syndrome) has not been described. I report two children (one with severe cyanosis from pulmonary arteriovenous malformations and the other with severe PAH) with cutaneous hemangioma and Abernethy syndrome. Hemangioma may be a clinical pointer to portosystemic shunts even in the absence of obvious liver disease.